2010
DOI: 10.1073/pnas.1012344107
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a receptor for an extinct virus

Abstract: The resurrection of endogenous retroviruses from inactive molecular fossils has allowed the investigation of interactions between extinct pathogens and their hosts that occurred millions of years ago. Two such paleoviruses, chimpanzee endogenous retrovirus-1 and -2 (CERV1 and CERV2), are relatives of modern MLVs and are found in the genomes of a variety of Old World primates, but are absent from the human genome. No extant CERV1 and -2 proviruses are known to encode functional proteins. To investigate the host… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…In the primate lineage, HERV-K(HML5) is estimated to have infected our ancestors some 55 Ma [55], and also carries a beta-type TM, suggesting a long association with mammals of retroviruses with non-covalently associated Env subunits [26]. Similarly, many examples of gamma-type TM sequences can be found among ERVs estimated to have been infectious tens of millions of years ago, such as an ERV of Bos taurus , BoERV1, that is estimated to have integrated into the germline of the ancestors of cattle between 58 and 126 Ma [56]; and the chimpanzee ERV, CERV1, estimated to have integrated as long ago as 82 Myr [57]. …”
Section: Transmembrane Typesmentioning
confidence: 99%
“…In the primate lineage, HERV-K(HML5) is estimated to have infected our ancestors some 55 Ma [55], and also carries a beta-type TM, suggesting a long association with mammals of retroviruses with non-covalently associated Env subunits [26]. Similarly, many examples of gamma-type TM sequences can be found among ERVs estimated to have been infectious tens of millions of years ago, such as an ERV of Bos taurus , BoERV1, that is estimated to have integrated into the germline of the ancestors of cattle between 58 and 126 Ma [56]; and the chimpanzee ERV, CERV1, estimated to have integrated as long ago as 82 Myr [57]. …”
Section: Transmembrane Typesmentioning
confidence: 99%
“…Given their phylogenetic relatedness, wild populations of non-human primates are an indicator species for monitoring emerging pathogens, providing crucial information on infectious diseases that may also affect humans (e.g. [1], [3][11]). …”
Section: Introductionmentioning
confidence: 99%
“…A second example of reconstruction, this time of 20-million-year-old TRIM5a, suggested that restriction of HIV-1 has decreased during evolution leading to humans (Goldschmidt et al 2008). Soll et al investigated two chimpanzee endogenous retrovirus-1 and -2 (CERV1 and CERV2) relatives of modern murine leukemia viruses (MLVs) that are present in the genomes of Old World primates, but absent from the human genome (Soll et al 2010). Using CERV2 Env-pseudotyped MLV vectors, Soll et al identified copper transport protein 1 (CTR1) as a receptor that was presumably used by CERV2 during its ancient exogenous replication in primates.…”
Section: Paleovirology and Protein Reconstructionmentioning
confidence: 99%